Evolution in adaptive landscapes: Examples of science and technology development - Andrea Scharnhorst (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2000)
In science and technology studies it is very common to describe structure formation and structure development by using spatial representations. Maps of such knowledge landscapes allow the dynamic character of the research processes to be visualized. In this paper, we discuss how concepts, methods and mathematical models that allow the dynamics and the evolution of complex systems to be described can be applied to this area. A special approach is considered, which we call geometrically oriented evolution theory (G_O_E_THE). First steps towards implementing this new method in the context of the development of national science systems are discussed. – – In Wissenschafts- und Technologieuntersuchungen wird für die Beschreibung von Strukturbildungs- und Strukturveränderungsprozessen häufig auf räumlich-geografische Metapher zurückgegriffen. Mit Hilfe von veränderlichen Wissenslandschaften lässt sich die Dynamik des wissenschaftlichen Suchprozesses veranschaulichen. In der vorliegenden Arbeit, wird die Anwendung von Konzepte, Methoden und mathematische Modelle aus der Komplexitätsforschung für die Beschreibung von Suchprozessen in Wissenslandschaften diskutiert. Ausgangspunkt bilden dabei sog. geometrisch orientierte Evolutionstheorien (G_O_E_THE). Erste empirische Anwendungen im Bereich der Entwicklung nationaler Wissenschaftssysteme werden präsentiert.
Keywords: 300